Relações entre eventos estressores precoces, sintomas psiquiátricos, esquemas iniciais desadaptativos e características de personalidade em amostra não clínica - Costa , Ismael Ferreira da (2016)
Investigations of etiological factors related to the development and maintenance of mental disorders receive special attention in the mental health field. Among the multiple motivators that influence the development of vulnerability for the emergence of mental disorders has been bombing for the presence of Early Life Stress (ELSs) as impact factor of the neurodevelopment of the individual. Despite the existing knowledge about this association, we have noticed less emphasis on the influence of these ELSs on Early Maladaptive Schemas (EMSs) and personality traits in people with this history. Given the frequency with which ELSs place in society and understanding the importance of this knowledge for the development of effective therapeutic measures for this audience, the aim of this study was to investigate possible relationships between ELSs, psychiatric symptoms, EMSs and personality characteristics nonclinical sample. This study is characterized as transversal, correlational and quantitative and a sample of 200 people of both sexes, aged between 18 and 30 years old and literate. Data collection was performed with the use of a sociodemographic questionnaire, the Inventory Self-Report for adults (ASRI), the Childhood Trauma Questionnaire (CTQ), the Young Schema Questionnaire (YSQ-S3) and the Inventory of Temperament and character (ITC-R). The results obtained from the indicate a greater presence of all psychiatric symptoms and disorder and EMSs the group of people with a history of ELSs, which was also characterized by lower scores in self-directedness, character factor associated with adequate maturity emotional. In The ELSs also showed significant positive associations with psychiatric symptoms, EMSs and Harm avoidance, temperament factor associated with emotional instability and increased vulnerability to developing mental disorders were also identified negative correlations between ELSs and character factors Selfdirectedness and Cooperativeness. The Multiple Regression Analysis showed a model where EMSs, Harm avoidance temperament factor and ELSs explain 69% of the variation of the psychiatric symptoms of the sample, from the adopted predictors, the EMSs was the largest contributor to this result, explaining 31 % of the presence of psychiatric symptoms followed by Harm avoidance to 25%. Through mediation analysis, it was found that most of the predictive power associated with ELSs can best be explained by the presence of EMSs and lower intensity for the Harm avoidance. It is suggested that much damage attributed to the ELSs is mediated by the action of multiple factors, in this study the presence of EMSs and Harm avoidance increase significantly the predictive power of psychiatric symptoms associated with the ELSs. Advocates is that way that handling is therapeutically these features possible minimize the deleterious effects of the presence of EEP.